Conrad Summenhart's theory of individual rights - Varkemaa, Jussi (Studies in medieval and Reformation traditions, 2012)
In recent decades scholars have shown considerable and steadily increasing interest in medieval discussions of rights. This book aims to make a significant contribution to scholarship by providing a detailed and systematic account of Conrad Summenhart's (1455-1502) language of individual rights. Starting from the view that Summenhart's Opus septipertitum contains a carefully constructed and comprehensive theory of individual rights, this study analyses Summenhart's theory in its historical context treating it as a culmination of late medieval discourse on individual rights. This study is particularly useful to scholars interested in the origin of human rights language and modern political individualism, as well as to all those who work in the field of late medieval and early modern political and moral philosophy. -- Book Cover.